Głos i jego wielowymiarowe konteksty = The voice and its multidimensional contexts - Kowalkowska, Iwona; Wyganowska-Świątkowska, Marzena (Zielona Góra: Instytut Pedagogiki. Wydział Pedagogiki, Psychologii i Socjologii. Uniwersytet Zielonogórski)
The article raises the matter of human voice in biological, cultural, artistic, spiritual and medical context. The authors would like to point out the relationships between all of its aspects. It is also an attempt to pay attention on the influence of voicing on the body of a man: which is making the transmission (in speech and singing) and the one who is listening (the recipient). The authors show the possibilities of self-therapy through the harmonisation of the biofield. Briefly they are also pointing out the technical difficulties of voicing and the difficulties of vocal education/training.
Keywords: wokalistyka; komunikacja; słowo; muzyka; dźwięk; oddech; mózg; autoterapia; vocalism; communication; word; lyrics; music; sound; breath; brain; self-therapy